Pengembangan Lembar Kerja Siswa dalam Menulisa Karya Ilmiah Berbasis Lokal Wisdom melalui Pendekata Genre Report dengan Media Video - Dara Dwi May Nanda; Liesna Andriany; Rita; Rika Kartika (Medan Resource Center, 2022)
This study aimed to describe the product of teaching materials development in the student’s worksheets based on local wisdom through a genre report approach in scientific writing material, to describe the response validation of the expert team of validators toward the prototype of teaching materials in the student’s worksheets in writing scientific papers based on local wisdom through genre report approach. The research method is 4-D research and development by Thiagarajan. This study used 3 stages, namely define, design, and development. At the development stage, it was only validated by four expert team validators. The data in this study is quantitative descriptive as the main data that collected by using an instrument with a Likert scale. The respondents consisted of material experts, design experts and media experts. The data analyzed using descriptive quantitative method and to calculate the average percentage of indicators used descriptive percentages. The results of developing a prototype worksheet’s students in writing scientific paper based on local wisdom through a genre report approach. It can be seen from the validation of the material experts by getting an average score as 91% with the criteria of